Metformin and AMP Kinase Activation Increase Expression of the Sterol Transporters ABCG5/8 (ATP-Binding Cassette Transporter G5/G8) With Potential Antiatherogenic Consequences. Issue 7 (July 2018) - Molusky, Matthew M.; Hsieh, Joanne; Lee, Samuel X.; Ramakrishnan, Rajasekhar; Tascau, Liana; Haeusler, Rebecca A.; Accili, Domenico; Tall, Alan R.
Abstract : Objective—: The mechanisms underlying the cardiovascular benefit of the anti-diabetic drug metformin are poorly understood. Recent studies have suggested metformin may upregulate macrophage reverse cholesterol transport. The final steps of reverse cholesterol transport are mediated by the sterol transporters, ABCG5 (ATP-binding cassette transporter G5) and ABCG8 (ATP-binding cassette transporter G8), which facilitate hepato-biliary transport of cholesterol. This study was undertaken to assess the possibility that metformin induces Abcg5 and Abcg8 expression in liver and to elucidate the underlying mechanisms. Approach and Results—: Metformin-treated mouse or human primary hepatocytes showed increased expression of Abcg5/8 and the bile salt export pump, Bsep . Administration of metformin to Western-type diet–fed mice showed significant upregulation of Abcg5/8 and Bsep . This resulted in increased initial clearance of 3 H-cholesteryl ester HDL (high-density lipoprotein) from plasma. However, fecal 3 H-cholesterol output was only marginally increased, possibly reflecting increased hepatic Ldlr (low-density lipoprotein receptor) expression, which would increase nonradiolabeled cholesterol uptake. Abcg5/8 undergo strong circadian variation. Available chromatin immunoprecipitation-Seq data suggested multiple binding sites for Period 2, a transcriptional repressor, within the Abcg5/8 locus. Addition of AMPK (5′ adenosine monophosphate-activated protein kinase) agonists decreased Period 2 occupancy, suggesting derepression of Abcg5/8 . Inhibition of ATP citrate lyase, which generates acetyl-CoA from citrate, also decreased Period 2 occupancy, with concomitant upregulation of Abcg5/8 . This suggests a mechanistic link between feeding-induced acetyl-CoA production and decreased cholesterol excretion via Period 2, resulting in inhibition of Abcg5/8 expression. Conclusions—: Our findings provide partial support for the concept that metformin may provide cardiovascular benefit via increased reverse cholesterol transport but also indicate increased Ldlr expression as a potential additional mechanism. AMPK activation or ATP citrate lyase inhibition may mediate antiatherogenic effects through increased ABCG5/8 expression. Abstract : Supplemental Digital Content is available in the text.